Can universal patient-held health booklets promote continuity of care and patient-centred care in low-resource countries? The case of Mongolia. Issue 9 (26th April 2019) - Ibrahim, Hussein; Munkhbayar, Uyanga; Toivgoo, Aira; Humphries, Claire; Ochir, Chimedsuren; Narula, Indermohan S; Lilford, Richard; Manaseki-Holland, Semira
Abstract : Background: A system of clinical records accessible by both patients and their attending healthcare professionals facilitates continuity of care and patient-centred care, thereby improving clinical outcomes. The need for such a system has become greater as the proportion of patients with chronic non-communicable diseases (NCDs) requiring ongoing care increases. This is particularly true in low-income and middle-income countries where the burden of these diseases is greatest. Objective: To describe a nationwide patient-held health booklet (PHHB) system and investigate its use and completeness for clinical information transfer during chronic NCD outpatient visits in Ulaanbaatar, Mongolia. Methods: Qualitative and quantitative methodologies were employed in this mixed-methods study. Structured interviews were used to study a sample of adult patients with chronic NCDs attending the outpatient departments (OPDs) of two large, public secondary care hospitals ; artefact reviews were used to analyse the content of the written documents relating to their clinical care; and snowball methodology was used to identify policy and training documents. Results: 96% (379/395) brought handover documentation from previous provider/s: 94% had PHHBs, 27% other additional documents and 4% had nothing. 67% were referred from primary care and 44% referred back for follow-up. On leaving the OPD, irrespective of requirements for computer data entry, doctors provided written clinical information in the PHHB for 93% of patients. 84% of patients recalled being given verbal information. However, only 41% of the consultation with written information included all three key handover information items (diagnosis, management/treatment and follow-up). The PHHBs were the best completed type of document, with evidence that they were consulted by patients (80%), public (95%) and private (77%) providers. Living >1 hour away (OR=0.28; 95% CI 0.13 to 0.61) decreased the likelihood of receiving written management/treatment information; living >1 hour away (OR=0.48; 95% CI 0.27 to 0.87), comorbidity (OR=0.55; 95% CI 0.35 to 0.87) and returning to secondary care (OR=0.52; 95% CI 0.33 to 0.80) all independently decreased the likelihood of receiving written follow-up information. A Ministry order mandates the use of the booklet, but there were no other related policies, guidelines or clinician training. Conclusion: The universal PHHBs were well accepted, well used and the best completed handover documentation. The PHHBs provided a successful handover option for patients with chronic NCDs in Mongolia, but their completeness needs improving. There is potential for global application.